DEWATA PANCANAMI DESAIN KAWASAN WISATA PANTAI TANGGAP BENCANA TSUNAMI DI TELUK PRIGI TRENGGALEK - Mohammad Rifqi Nur Afadiansyah (Jurnal Proyek Teknik Sipil, 2020)
The southern coast of Indonesia is an area prone to earthquakes with the potential for tsunamis. The tsunami disaster on the south coast has occurred in Pangandaran (2006) and the Sunda Strait, Banten (2018), which resulted in many casualties and material losses. DEWATA PANCANAMI is planned to create a coastal tourism pilot area that is responsive to the tsunami disaster and has an educational and aesthetic value. The study location is in the area of Prigi Beach, Trenggalek. This area is one of the tourist attractions that is crowded with visitors, but has the potential for a tsunami disaster. The data needed is the coastal layout, analysis of the potential for earthquakes and tsunamis, tsunami modeling, and the response of the community around the coast if DEWATA PANCANAMI is applied. This design consists of a breakwater equipped with a sensor detector, an aesthetically pleasing barrier fence, and a wave-resilient coastal structure. Especially for a wave breaker built in near coastal waters, the mechanism of action is to reduce energy and reduce wave height. Based on the analysis model and research location data, DEWATA PANCANAMI can be applied as a model for coastal areas with early warning systems, breakwaters, and aesthetic tsunami resistant buildings